Предмет: Математика,
автор: Аноним
решить уравнение
![\frac{7 - 3y}{4} = \frac{y + 6}{ - 1} \frac{7 - 3y}{4} = \frac{y + 6}{ - 1}](https://tex.z-dn.net/?f=+%5Cfrac%7B7+-+3y%7D%7B4%7D+%3D++%5Cfrac%7By+%2B+6%7D%7B+-+1%7D+)
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
4*(y + 6) = -1*(7 - 3y)
4y + 24 = -7 + 3y
4y - 3y = -7 - 24
y = -31
jekadva:
пожалуйста
Похожие вопросы
Предмет: Українська мова,
автор: oran
Предмет: Английский язык,
автор: Аноним
Предмет: Другие предметы,
автор: iksmary
Предмет: Алгебра,
автор: zhenya988
Предмет: Химия,
автор: 27122001dAn2